Uncovering the diuretic potential of Abutilon hirtum leaves extract in wistar albino rats (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Abutilon hirtum, traditionally recognized for its alleged diuretic effects, underwent examination to assess its viability as a natural substitute for synthetic diuretics. The methanolic extract of A. hirtum leaves (AHME) was methodically prepared using Soxhlet extraction technique and assessed for its diuretic activity in wistar albino rats. Five different groups were created from the animals: a control group, a standard group that received furosemide, and three test groups that received 150, 300 and 450 mg/kg of body weight of AHME. The evaluation of diuretic activity was conducted through the lipschitz test, which involved measuring various parameters including urine volume, pH, electrolyte excretion, diuretic effect and lipschitz value. The highest dose (450 mg/kg) substantially raised urine volume, electrolyte excretion, and pH compared to the control, with a Lipschitz value of 2.35. These results corroborate the traditional use of A. hirtum leaves and provide a basis to subsequent pharmacological research by confirming their diuretic ability.